2017
DOI: 10.5380/abclima.v21i0.49125
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidades E Tendências Climáticas Nos Máximos Do Inverno E Verão No Brasil

Abstract: As mudanças climáticas observadas em diferentes escalas têm atraído o interesse de muitos pesquisadores nas últimas décadas. Alterações nos padrões diário, mensal e sazonal de temperaturas do ar e de precipitação pluviométrica podem afetar as mais diversas atividades humanas. O objetivo desse estudo foi identificar tendências climáticas em séries anuais de junho e dezembro de precipitação pluvial e temperaturas máxima, mínima e média do ar de 243 localidades espalhadas pelo Brasil. Os meses de junho e dezembro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Neves et al (2016), studying 28 municipalities in the Paraná state, South Brazil, with maximum and minimum air temperature series, similar to the study by Ávila et al (2014), in the period from 1980 to 2009, observed alterations in most of these stations, from reductions, with rates up to -0.5ºC. Penereiro et al, 2017 working with series of maximum and minimum temperatures and temperatures and media in 243 locations distributed throughout the territory of Brazil, observing the absence of trends in rainfall stations. However, there is a high probability of an increase in minimum temperatures (34.16% of localities), media (35.39% of localities) and maximum (35.39% of localities).…”
Section: Introductionmentioning
confidence: 63%
“…Neves et al (2016), studying 28 municipalities in the Paraná state, South Brazil, with maximum and minimum air temperature series, similar to the study by Ávila et al (2014), in the period from 1980 to 2009, observed alterations in most of these stations, from reductions, with rates up to -0.5ºC. Penereiro et al, 2017 working with series of maximum and minimum temperatures and temperatures and media in 243 locations distributed throughout the territory of Brazil, observing the absence of trends in rainfall stations. However, there is a high probability of an increase in minimum temperatures (34.16% of localities), media (35.39% of localities) and maximum (35.39% of localities).…”
Section: Introductionmentioning
confidence: 63%
“…The region's climate is classified as AW according to Köppen's classification with well-defined dry (May to October-average values ranging from 3 to 13 mm) and rainy (November to April-average values ranging up to 219 mm) seasons. The mean annual precipitation is 1552 mm, where monthly means range from 9 mm in June to 249 mm in December [25]. Soils in the study site are mainly Oxisols [26] (U.S. soil classification system) or Red Latosols [27], characterized by high acidity and low nutrient (e.g., phosphorus-P) availability.…”
Section: Study Sites Descriptionmentioning
confidence: 99%
“…Also, the edaphic fauna diversity is considered a key aspect for maintaining the structure and fertility of tropical soils, especially in nutrient-poor soil as a major part of Cerrado that is covered by latossolos (oxisoils), presenting potentially faster responses than other soil attributes, therefore serving as biological indicators sensitive to ecological changes in agrosystems [22][23][24][25]. In this context, the study of possible impacts on soil mesofauna is extremely important to better understand the impacts of eucalyptus plantations in the Cerrado ecoregion.…”
Section: Introductionmentioning
confidence: 99%
“…Regiões que apresentam irregularidade na distribuição das chuvas, necessitam de um planejamento para plantio das culturas, de modo que o plantio seja realizado no momento de maior disponibilidade hídrica, evitando que as fases de maior demanda hídrica da cultura não correspondam com o período de deficiência de água no solo (Ribeiro et al, 2015). Regiões que desenvolvem atividade agrícola, onde em determinado período do ano apresentam deficiência hídrica do solo, devem ter o seu déficit suprido com uso da irrigação, de forma a garantir a produtividade das lavouras (Ferreira et al, 2021).…”
Section: Tipos Climáticos íNdice De Umidade (Im)unclassified